APPLICATION OF INNOVATIONS IN CULTURAL TOURISM - Konstantinova, Yoana (E-Journal VFU, 2024)
This article contributes to the academic debate on innovation in cultural tourism. Themain goal of the research is to establish the potential for innovative development of cultural763tourism in tourist destinations. A model for evaluation and analysis of cultural tourism in touristdestinations has been proposed.An empirical approach was used to achieve the set goal. The results show that culturaltourism provides a wide range of opportunities for innovation which should contribute to itsdevelopment. The proposed model can be successfully used for identifying problematic areasand implementing effective innovation solutions. For the purposes of the research, sources inseveral languages were used, including Bulgarian, English, Italian and Russian.
Keywords: tourist destination; cultural tourism; innovation